Modeling and simulating a new process for extracting phenols from model coal tar by low-boiling-point amine aqueous solutions. (1st September 2021) - Li, Yonglin; Ai, Qiuhong; You, Kuiyi; Zhao, Fei; Xiao, Wenlong; Luo, He'an
Highlights: The green process for extracting phenols from model coal tar by low-boiling-point amine aqueous solution was proposed. The Wilson model and UNIF-DMD model selected by the VLE and LLE data were used to simulate the design process. The molecular structure of low-boiling-point amine and the neutral components in coal tar had great influence on the design process. Favorable comparison with traditional alkaline washing process. Abstract: In this paper, a green, efficient, and simple process for extracting phenols from coal tar using low-boiling-point amine aqueous solution as the extractant has been developed. The vapor–liquid-equilibrium (VLE) data of the ethylamine-water-phenol ternary system and the liquid–liquid-equilibrium (LLE) data of phenols extracted by aqueous ethylamine from model oil were measured. The Wilson model for the VLE and UNIF-DMD model for the LLE were selected to simulate the designed process by data regression or relative deviation method. The simulation results showed that the designed process was economical and environmentally-friendly. Under the optimal conditions, the extraction yield of phenols was 97.9%, the recovery rate of ethylamine and water were 99.7% and 91.7%, and the unit production cost was 326.0 CNY·t −1, which was only 25% that of the alkali washing method. More importantly, there is no "three waste" emission in theory. In addition, the effects of multiple low-boiling-point amines and neutral oil components with different polarities on the design process were discussed. The results showed that organic amines with a low boiling point, strong hydrophilicity and strong alkalinity were beneficial to the process, while the polar components in neutral oil negatively affected the process.